Emerging Subspecialties in Neurology: Global health - Siddiqi, Omar K. (Lippincott Williams & Wilkins, 2013)
Global health is the study, research, and practice that places a priority on improving health and achieving equity in health for all people worldwide.(1) In contrast to the public health concerns of a particular country or region, global health looks at populations irrespective of borders. One of the key elements in advancing the field of global health was the establishment of the WHO in 1948. Since its inception, the WHO has helped coordinate global efforts toward eradication of diseases such as smallpox and polio as well as elimination of onchocerciasis. It now assumes responsibility for the International Classification of Diseases. More recently, the field of global health has received considerable attention from world leaders, philanthropists, and academics. In 2009, President Obama introduced his Global Health Initiative that proposed spending $63 billion over 6 years to support global health programs specifically targeting areas such as HIV/AIDS, malaria, tuberculosis, nutrition, and reproductive health. On his first day of work as NIH Director, Francis Collins announced global health as one of his 5 themes of “exceptional opportunity” that would receive special priority during his tenure.(2) The Fogarty International Center is a branch of the NIH that helps to support global health research for US and foreign researchers, often in resource-limited settings. The research initiatives encompass a diverse range of disciplines within the field of medicine.